Effect of Hemodialysis on Pharmacokinetics of Ezogabine/Retigabine and its N-Acetyl Metabolite in Patients with End Stage Renal Disease - J. Tompson, Debra; Buraglio, Mauro; Bullman, Jonathan; S. Crean, Christopher; Rayner, Kirsty (Current Clinical Pharmacology, 2014)
Ezogabine (EZG)/retigabine (RTG) and its metabolites are mainly eliminated renally. This Phase 1 study assessed the effect of hemodialysis on the pharmacokinetics of EZG/RTG and its N-acetyl metabolite (NAMR) in patients with end-stage renal disease; tolerability of EZG/RTG was a secondary endpoint. Patients (N=8) received EZG/RTG 100 mg orally 4 hours before (Period 1) or following (Period 2) dialysis. Blood (both periods) and dialysate (Period 1) samples were taken up to 68 hours post dose. Tolerability was assessed throughout both periods. The area under the concentration– time curve (0–68 hours) for EZG/RTG was 33% lower (geometric mean ratio [90% confidence interval]: 0.67 [0.61, 0.73]) on dialysis versus off dialysis and 43% lower for NAMR (0.57 [0.53, 0.62]). Median (range) reductions in plasma concentrations from dialysis start to end were 52% (17–59%) for EZG/RTG and 51% (27–72%) for NAMR. EZG/RTG 100 mg was generally tolerated.
Keywords: tolerability